Avaliação da implementação do regulamento técnico de boas práticas para serviços de alimentação - Saccol, Ana Lúcia de Freitas (2013)
According to the Collegiate Directory of Brazilian Health Surveillance Agency (acronym in Portuguese: Anvisa), the Good Practices are procedures that should be adopted by food services to ensure the sanitary quality of foods and compliance with sanitary regulations. In this context, in the present study, the purpose was to evaluate the implementation of the Technical Regulation of Practice for Food Services at the federal level. The research was conducted in 26 states and the Federal District, among August 2009 and November 2012. Initially, it was done a meeting with Anvisa in order to seek support for the work. After, there was contact by e-mail and/or phone with all health surveillance agencies of the states, capitals and the Federal District, where the research was conducted, it is invited to participate and sent the questionnaire pattern previously tested. In health surveillance showed that complementary legislation, held a meeting spot with simultaneous recording and interview. It was also applied a standard questionnaire, previously tested with all consultants linked to a program of consultancy Best Practices nationwide. With these instruments, it was obtained a survey of developed strategies, strengths and weaknesses in relation to the implementation of Resolution nº 216/2004 of Anvisa. It was performed an evaluation and comparison of complementary laws found and proposed adjustments to the legislation. Through the survey, it was found that the states of São Paulo, Santa Catarina and Rio Grande do Sul have complementary laws, as well as the capital of São Paulo. Relevant experience was verified as performing actions in specific areas, partnerships and training in best practices, as well as some weaknesses, particularly the lack of knowledge and commitment of those responsible for food services, as well as the lack of specifications some items. It was observed the importance of the publication of Roadmaps Inspection by coordinators. It was noted that the laws of the state and the city of São Paulo are distinguished by specifying requirements of federal law and the order of the Rio Grande do Sul also by regulating capabilities. It was verified aspects related to difficulties with the managers of food services, health authorities and the lack of time and temperature criteria. It was confirmed then the need for federal regulation of Practice for Nutrition and Dietetics Services Hospital. In short, it was believed that this study provides the basis for future projects and provides the exchange of experiences depending on the stocks that had positive impact during the application of the Regulation, as well as the difficulties reported. However, many of the weaknesses that were mentioned can be solved by their own state and local health surveillance through the publication of their own regulations.